Становлення мережевої економіки в умовах глобалізації - Данилович-Кропивницька, М. Л. (Видавництво Львівської політехніки, 2015)
У статті, на основі систематизації тенденцій розвитку глобалізації та виділення її істотних ознак, запропоновано авторське визначення терміну “глобалізація”. Запропоновано графічну модель, яка ілюструє послідовність та підпорядкованість у зміні форм розвитку сучасної економіки. У цій моделі виділено доіндустріальні суспільства, суспільства на ранній стадії індустріалізації, індустріальні, масового споживання, постіндустріальні в початковій стадії та інформаційні. Термін “інформаційне суспільство” розкриває значення інформації як самостійної фундаментальної сутності й перетворення її на реальний економічний ресурс. Через аналіз розвитку інформаційного суспільства, обґрунтовано перехід до мережевої економіки як нового підходу до вирішення проблем конкуренції в умовах глобалізації економіки. This article suggests an author’s approach to the definition of globalization basing on systemizing the tendencies of globalization development and identifying its key features. It is vital for Ukraine to consider the processes of globalization while working on its own national innovation development strategy and present-day economic policies. The study presents a graph model that illustrates a sequence and subordination in the changing framework of modern economy. This model reviews pre-industrial societies, societies at the early stage of industrialization, industrial, mass consumption, post-industrial at the early state and information societies. The term ‘information society’ clarifies the meaning of information as an independent fundamental essence and its ability to transform into a real economic resource. Information systems have become strategic elements and key means for creating value for many industries that make “network economy”. The expansion of the fifth waves of innovation when computer and information technologies, new organizational structures, space communication technologies, optical fiber and biotechnologies took a leading role was a crucial condition for establishing “network economy”. While analyzing the establishing of the information society it rationalizes the transition to the network economy to be a new solution for solving the problems of competition under globalization of economy.
Development of network economy under globalization
Keywords: глобалізація; інформаційне суспільство; мережева економіка; globalization; information society; network economy